Prognoses and risk stratification of thrombus‐associated events in heart failure patients without atrial fibrillation - Yanxuan Li; Zihan Li; Daoyuan Si; Ping Yang (ESC Heart Failure)
Abstract Aims We aim to assess the risk of thrombus‐associated events (TAE) in patients with heart failure (HF) without atrial fibrillation (AF) and develop an effective scoring system for a risk stratification model. Methods and results This retrospective study included 450 patients (median age 64.0 years, interquartile range [55.0, 75.0]; 31.6% women) hospitalized for HF without AF and atrial flutter, but with a left ventricular ejection fraction (LVEF) ≤ 55% and New York Heart Association (NYHA) functional class of III–IV. A median follow‐up of 47 months was conducted. In the present study, TAE during follow‐up was independently associated with both all‐cause death [hazard ratio (HR) 1.756, 95% confidence interval (CI) 1.324–2.328, P < 0.001] and readmission for HF (HR 1.574, 95% CI 1.122–2.208, P = 0.009) after adjustment for covariates. Hypertension (HR 1.573, 95% CI 1.018–2.429, P = 0.041), atrial arrhythmia excluding AF (AAexAF) (HR 2.041, 95% CI 1.066–3.908, P = 0.031), previous ischaemic stroke (HR 2.469, 95% CI 1.576–3.869, P < 0.001), and vascular disease (HR 1.658, 95% CI 1.074–2.562, P = 0.023) were independently associated with TAE. Age (HR 1.021, 95% CI 1.008–1.033, P = 0.001), previous ischaemic stroke (HR 1.685, 95% CI 1.248–2.274, P = 0.001), LVEF ([10, 25] vs. [40, 55]) HR 1.925, 95% CI 1.311–2.826, P = 0.001; (25, 40] vs. (40, 55] HR 1.084, 95% CI 0.825–1.424, P = 0.563), and creatinine clearance rate (Ccr) (HR 0.991, 95% CI 0.986–0.996, P = 0.001) were independently associated with composite events of TAE and death (TAE‐D). CHA2DS2VASc modestly predicted 5‐year TAE [area under the receiver operating characteristic curves (AUC) 0.660, P < 0.001 compared with 0.5] and TAE‐D (AUC 0.639, P < 0.001 compared with 0.5). (C)ACE, formed by incorporating AAexAF, LVEF, and Ccr into CHA2DS2VASc, had higher AUC for predicting 5‐year TAE (0.694 vs. 0.660, P = 0.018) and TAE‐D (0.708 vs. 0.639, P < 0.001) compared with CHA2DS2VASc. In patients with HF with reduced ejection fraction (HFrEF), (C)ACE and (C)ACEN [formed by incorporating NYHA into (C)ACE] had higher AUC compared with CHA2DS2VASc in predicting 5‐year TAE (0.700 and 0.707 vs. 0.649, P = 0.013 and 0.030, respectively) and TAE‐D (0.712 and 0.713 vs. 0.622, P < 0.001 and <0.001, respectively). The AUC did not improve statistically from (C)ACE to (C)ACEN (0.700 vs. 0.707, P = 0.600 for TAE; 0.712 vs. 0.713, P = 0.917 for TAE‐D). Conclusions In HF without AF, TAE during follow‐up was associated with adverse prognoses. The independent risk factors of TAE or TAE‐D improved CHA2DS2‐VASc predictive ability, especially in patients with HFrEF. Our findings provide new evidence for TAE risk stratification in HF without AF, potentially guiding prophylactic anticoagulation.